Identification of Pests and Diseases Crystal Guava (Psidium guajava L.) in Ngargoyoso District, Karanganyar Regency - Nur Rokhimah Hanik; Rindi Diah Ayu Fitriani; Fiky Ariska Cahyanti; Desty Oktavianingtyas; Tri Wahyuni; Siti Nur Hidayati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Pests and diseases that attack Crystal Guava are the main obstacles in increasing agricultural productivity, as well as disrupting plant physiology and growth. The purpose of this study was to identify pests and diseases of crystal guava (Psidium guajava L). The study was conducted for 3 months, (June-August) 2022 in three crystal guava gardens in Gemawang Village, Dukuh, Ngargoyoso District, Karangayar. Data were obtained from observations of guava plant samples crystals and fruit attacked by pests and diseases, as well as interviews with owners and managers to obtain information about cultivation from planting to harvest. The results of the research found several pests of Crystal Guava (Psidium guajava L.), including: Frogs (Cynopterus spp.), Fruit flies (Bactrocera dorsalis), caterpillars (Setora nitens), ladybugs (Helopeltis sp.), sac caterpillars (Lepidopthera: Psychide), shoot caterpillars (Lepidoptera: Pyralidae), and mealybugs (Paracoccus marginatus). morphology due to nutrient deficiency (potassium/magnesium); black spot and fruit rot by the fungus Collectrichum gleosporioides Penz, fruit canker (scab) Pestalotiopsis psidii (pat) Mordue, red rust by the algae Chephaleurus virescens, wilt disease by the algae Fusarium sp, and the fungus Cercospora psidii. Treatment was carried out once a week, by applying NPK and gandasil fertilizers and spraying with regent 50 insecticides, Yasithrin and Fostin. as well as wrapping young fruit. Pests and diseases found in Crystal Guava plantations in this study can reduce production, therefore the results of this study can be used as information material for novice farmers who want to develop Crystal Guava picking tours both on plantations and in their yards.